A new compression strategy to reduce the size of nanopore sequencing data - Jayasooriya, Kavindu; Jenner, Sasha P.; Marasinghe, Pasindu; Senanayake, Udith; Saadat, Hassaan; Taubman, David; Ragel, Roshan; Gamaarachchi, Hasindu; Deveson, Ira W. (Genome Research, 2025)
Nanopore sequencing is an increasingly central tool for genomics. Despite rapid advances in the field, large data volumes and computational bottlenecks continue to pose major challenges. Here, we introduce ex-zd, a new data compression strategy that helps address the large size of raw signal data generated during nanopore experiments. Ex-zd encompasses both a lossless compression method, which modestly outperforms all current methods for nanopore signal data compression, and a ‘lossy’ method, which can be used to achieve additional savings. The latter component works by reducing the number of bits used to encode signal data. We show that the three least significant bits in signal data generated on instruments from Oxford Nanopore Technologies (ONT) predominantly encode noise. Their removal reduces file sizes by half without impacting downstream analyses, including basecalling and detection of modified DNA or RNA bases. Ex-zd compression saves hundreds of gigabytes on a single ONT sequencing experiment, thereby increasing the scalability, portability, and accessibility of nanopore sequencing.